Sciatic endometriosis induces mechanical hypersensitivity, segmental nerve damage, and robust local inflammation in rats - Chen, S. (Eur J Pain, 2015)
BACKGROUND: Endometriosis is a common cause of pain including radicular pain. Ectopic endometrial tissue may directly affect peripheral nerves including the sciatic, which has not been modelled in animals. METHODS: We developed a rat model for sciatic endometriosis by grafting a piece of autologous uterine tissue around the sciatic nerve. Control animals underwent a similar surgery but received a graft of pelvic fat tissue. RESULTS: The uterine grafts survived and developed fluid filled cysts; the adjacent nerve showed signs of swelling and damage. Mechanical and cold hypersensitivity and allodynia of the ipsilateral hindpaw developed gradually over the first two weeks after the surgery, peaked at 2 to 5 weeks, and was almost resolved by 7 weeks. Control animals showed only minor changes in these pain behaviors. Histological signs of inflammation in the uterine graft and in the adjacent nerve were observed at 3 weeks but were resolving by 7 weeks. In vivo fiber recording showed increased spontaneous activity, especially of C fibers, in sciatic nerve proximal to the uterine graft. Several pro-inflammatory cytokines including interluekin-18, VEGF, fractalkine, and MIP-1α, were elevated in the uterine graft plus sciatic nerve samples, compared to samples from normal nerve or nerve plus fat graft. Growth associated protein 43 (GAP43), a marker of regenerating nerve fibers, was observed in the adjacent sciatic nerve as well as in the uterine graft. CONCLUSIONS: This model shared many features with other rat models of endometriosis, but also had some unique features more closely related to neuropathic pain models.